Review of design and manufacturing of superabsorbent polymers (SAPs) hydrogel for agriculture in arid areas - Maysa Muhammad; Medhat Tawfic; Mohamed Taha; Ahmed Elsabbagh (Discover Materials)
Abstract This review aims to be a reference article on designing and manufacturing different SAP materials for use in agriculture. The structure used for the content described reveals significant progress in the agricultural sector in recent years. SAP materials to enhance sandy soil compactness, topology, and mechanical properties (swelling, water harvesting, and nutrient release). SAPs in agriculture also promote a 60–80% swelling rate, slow release of nutrients for plants to last longer, and maximum water retention. This systematic review examined methods for designing, manufacturing, and processing SAPs for their properties and impact on agriculture in arid areas and plant growth. SAP materials are designed and manufactured in three morphologies. The first is the preparation of technical processes for manufacturing SAP (hydrogel) powder. Second, SAPs are prepared by mixing the monomer solution and crosslinking agent and converting the SAP solution into fibers using an electrospinning machine and wet spinning technique. Finally, the sheet was produced using a spun lace (hydroentangling) machine that converts SAP fibers into sheets. Similarly, the production processes used a spun-bond machine that converts SAP powder into sheets and a sheet modeling machine that converts SAP fibers into SAP sheets. Furthermore, many SAP materials used for agriculture in arid areas, functional monomers, initiators, and cross-liner agents can be manufactured as powders, fibers, and sheets and have high success rates. This is demonstrated by the excellent maximum absorbent capacity, and maximum water retention of the sheets, followed by those of the fibers and powders. This is supported by the quantitative standards for SAP morphology manufacturing process cost, water absorption, and water retention time. Graphical Abstract